INTENSITAS DAN PREVALENSI EKTOPARASIT Balanus sp. PADA KERANG HIJAU YANG DIBUDIDAYAKAN DALAM BAGAN TANCAP DI PERAIRAN BANYUURIP, UJUNGPANGKAH, GRESIK - Shofiyah, Badriyatus; Farikhah, Farikhah; Safitri, Nur Maulida (Jurnal Perikanan Pantura (JPP); Vol 5 No 1 (2022): MARET 2022DO - 10.30587/jpp.v5i1.3847, 2022)
Green mussels, as one of several food source in Indonesia and cultured by stake cultures, are susceptible to barnacles Balanus sp. The purpose of this study was to analyze the population of Balanus sp. related to the amount of them attached to the clam shells in various length classes of green mussels, determine the intensity and prevalence of Balanus sp. on green mussels, and analyzed the correlation between length and total weight of green mussels Perna viridis to Balanus sp. The study was conducted at Banyuurip Beach, Ujungpangkah District, Gresik Regency in June-July 2021. The sampling interval was set once every 20 days on each stake culture. The selected stake culture was determined by purposive sampling; with the sample are green mussels and Balanus sp. The variable of this research is the number of Balanus sp. attached to the shell on various classes of mussel length, intensity, prevalence, biometry and correlation between length and weight, correlation between height and total weight, correlation of width and total weight of green mussels attached by Balanus sp. Data analysis was done by the T-test and correlation. The results showed that The 1st stake culture was dominated by barnacles Balanus sp. in class VII of green mussel length (47.7 – 55.4)mm. The 2nd stake culture was dominated by barnacles in class VII green mussel length (47.7 – 55.4)mm. The 3rd stake culture was dominated by barnacles Balanus sp. in the green mussel length class VI (39.9 – 47.6)mm. The intensity of attack by Balanus sp. on green mussels showed an average value of 7±3.54 individual/tail on 1st stake, and 8±7.78 individual/tail on 2nd stake. Both are considered to be a moderate intensity. The highest prevalence of barnacles Balanus sp. was in the 1st stake, with the score of 51%±46.67, and was included in the very frequent category. As the conclusion, this results showed that the presence of the ectoparasite Balanus sp. has a moderate effect on green mussels growth, which shown a disturbance in the length and the width of green mussels.